2021
DOI: 10.2174/1871530320666200910110337
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rates of Coronary Artery Calcium Score in Patients with Non - Functioning Adrenal Incidentaloma

Abstract: Aim: We evaluated cardiovascular (CV) risk stratification for nonfunctioning adrenal incidentalomas (NFAIs) via the coronary-artery-calcium (CAC) score. Materials and Method: The participants were patients with an NFAI (n = 55). They were compared to patients with chest pain, a low-intermediate Framingham-risk score and a non-diagnostic treadmill-exercise test, which served as the control group (n = 49). Subsequently, the NFAI group was subdivided according to a CAC score of <100 Agatston units – mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Similarly, findings were reported in another study comparing 35 NFAI and 35 healthy controls, where the carotid intima‐media thickness, pulse wave velocity and augmentation index were significantly higher in NFAIs than in the control group 18 . There is even one study that showed similar prevalence of hypertension in patients with ACS and NFAIs 35 . Moreover, Bernini et al 33 demonstrated a significant reduction in systolic blood pressure and weight after the intervention in patients with NFAIs who underwent adrenalectomy.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Similarly, findings were reported in another study comparing 35 NFAI and 35 healthy controls, where the carotid intima‐media thickness, pulse wave velocity and augmentation index were significantly higher in NFAIs than in the control group 18 . There is even one study that showed similar prevalence of hypertension in patients with ACS and NFAIs 35 . Moreover, Bernini et al 33 demonstrated a significant reduction in systolic blood pressure and weight after the intervention in patients with NFAIs who underwent adrenalectomy.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, a large longitudinal follow‐up study found that patients with NFAI had higher BMI compared to age‐ and sex‐matched controls without adrenal tumours (25.1 vs. 24.0 kg/m 2 ) 13 . Similarly, two observational studies reported a similar prevalence of dyslipidaemia in patients with ACS and NFAIs 9,35 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations